Peran E-Money Dalam Meningkatkan Efisiensi Keuangan Pesantren Al-Amien Prenduan Madura Perspektif Ekonomi Syariah - Nadhifah, Siti Nurun; Andriani; Niawati, Irma; Salmaria, Elsa Syahrika; ‘Alamiah, Fawallia ‘Ansyarril (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – This study aims to analyze the role of the e-money system in improving the efficiency and transparency of financial management at the Al-Amien Prenduan Islamic Boarding School, and to examine its suitability with the principles of Islamic economics. Design/Methods/Approach – This study uses a qualitative approach with a descriptive method. Data were obtained through in-depth interviews, participant observation, and documentation related to the digital financial system of the Islamic boarding school. Findings – The main findings show that the implementation of e-money significantly simplifies financial transactions, reduces the risk of recording errors, speeds up services, and improves the security and supervision of funds. From a sharia economic perspective, the e-money system used is free from elements of riba (usury), gharar (uncertainty), and maysir (gambling), thereby supporting halal, educational, and productive transactions. Research Implications/Limitations – This study is limited to one Islamic boarding school location with subjective qualitative methods, and the cross-sectional research time limits the ability to generalize the findings and understand long-term developments comprehensively, so the results are less generalizable. Originality/Value – The implementation of e-money at Al-Amien Islamic Boarding School supports the efficiency and transparency of Islamic finance. However, sustainable development requires system improvement, innovation, and more intensive Islamic financial education. This finding is a model for the digitalization of Islamic boarding school finances that is used as a reference for other Islamic educational institutions in strengthening Islamic financial inclusion practically and adaptively.